2010
DOI: 10.1002/ptr.3280
|View full text |Cite
|
Sign up to set email alerts
|

Chemopreventive activity of Azadirachta indica on two‐stage skin carcinogenesis in murine model

Abstract: The present study reports the chemopreventive activity of aqueous Azadirachta indica leaf extract (AAILE) in a murine two-stage skin carcinogenesis model. Skin tumors were induced by topical application of 7,12-dimethylbenz(a)anthracene (DMBA) (500 nmol/100 µL for 2 weeks) followed by 12-O-tetradecanoylphorbol-13-acetate (TPA) (1.7 nmol/100 µL of acetone, twice weekly) as a promoter. Male LACA mice were divided into four groups: control, DMBA/TPA, AAILE and AAILE + DMBA/TPA. AAILE was administered orally at a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 42 publications
2
21
0
Order By: Relevance
“…Alanine and aspartate transaminases (ALT; AST), creatinine, albumin and globulin levels were not affected, but urea levels increased. The number of circulating lymphocytes were also raised (Table 2), which could be accredited in part to the immunomodulatory action of plant polysaccharides (Arora et al, 2011). In conclusion, TPL and FI fractioned from A. indica seed tegument exhibited potent anti-inflammatory activity, interfering not only in vascular, but especially in cellular inflammatory events, involving serotonin, PGE 2 and NO.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Alanine and aspartate transaminases (ALT; AST), creatinine, albumin and globulin levels were not affected, but urea levels increased. The number of circulating lymphocytes were also raised (Table 2), which could be accredited in part to the immunomodulatory action of plant polysaccharides (Arora et al, 2011). In conclusion, TPL and FI fractioned from A. indica seed tegument exhibited potent anti-inflammatory activity, interfering not only in vascular, but especially in cellular inflammatory events, involving serotonin, PGE 2 and NO.…”
Section: Resultsmentioning
confidence: 88%
“…In folk medicine, oil seeds, bark and leaf extracts have been used to treat gastrointestinal, analgesic and inflammatory disorders. Experimental data demonstrated immunomodulator and anti-infl ammatory activities of bark and leave extracts and also antipyretic and anti-infl ammatory effects of oil seeds (Arora et al, 2011;Biswas et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Aloe vera administration may be responsible for suppression of oxidative stress induced by X‐ray irradiation (Dadupandhi, ). It has been documented that ionising radiation induces metabolic oxidative stress and apoptosis in the dividing cells (Agrawal & Kale, ; Arora et al, ). Previous studies showed TUNEL‐positive cells or bodies in irradiated animals (Jiang et al., ; Kim et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Also, at the time point of 10 weeks (i.e. after 8 weeks of DMBA/TPA treatment when the papillomas begin to appear), it was observed that the skin of AAILE + DMBA/TPA‐treated animals exhibited an increase in lipid peroxidation levels when compared to the DMBA/TPA‐treated skin. Although this increase was statistically non‐significant, it may be emphasized that A. indica persistently keeps the lipid peroxidation levels high, in an attempt to prevent the damaged cells from thriving.…”
Section: Discussionmentioning
confidence: 99%